Jamaica : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
This 2005 Article IV Consultation highlights that the economic activity in Jamaica has been adversely affected by shocks. Real GDP contracted sharply in late 2004 following the devastating effects of Hurricane Ivan. Thereafter, while output recovered, it was dampened by the poor performance of agriculture, which suffered from adverse weather conditions. The nominal exchange rate has depreciated in recent months. Fiscal targets have been missed, and the monetary policy has been geared at containing inflation while also seeking to engender a sustainable reduction in interest rates.